VARIABILITY OF RACIAL COMPOSITION OF SUNFLOWER BROOMRAPE (ОROBANCHE CUMANA WALLR.) AND NEW STRATEGIES FOR PROTECTION FROM THE PARASITE - S. G. Hablak; Y. A. Abdullaeva; I. S. Riabovol (Вавиловский журнал генетики и селекции)
Sunflower broomrape is a parasitic chlorophyll plant that affects the root system of the host plant, absorbing water, nutrients and toxic products from it. Germination of broomrape seeds occurs due to strigolactones released into the soil by the roots of sunflower, which attracts arbuscular mycorrhizal fungi (AM-fungi). Strigolactones are substances of the “hunger” of plants and belong to a new class of phytohormones involved in many physiological processes, including the regulation of the availability of nutrients by the roots. The specific receptor KARRIKIN INSENSITIVE2 DIVERGENT (KAI2d) was identified in the broomrape, which is involved in the differential recognition of root sunflower exudates. Several genes of KAI2d have been established in the parasite genome, which encode the KAI2d receptors. As a result of the discovery of substances involved in the germination of broomrape seeds, new strategies for protecting sunflower from this parasitic plant are being discussed, which are under development. On the basis of strigolactones, a synthetic preparation, GR24, and its analogues have been created with the aim of introducing them into the soil to stimulate germination of broomrape seeds. The amino acid methionine strongly inhibits the early development of broomrape without a phytotoxic effect in sunflower. Seeds of broomrape are less likely to recognize the roots of sunflower, which are colonized by AM fungi, bacteria Rhizobium leguminosarum, Azospirillum brasilense due to a change in the composition of root exudates in colonized plants. Of great interest among the synthesized elicitors is acibenzolar-S-methyl. It causes systemic resistance to bacterial, fungal and viral diseases, induces the synthesis of PR proteins, and also activates the protective reactions of sunflower to the introduction of broomrape and leads to lignification of the endoderm and inhibition of haustoria of the broomrape seeds through the cell wall of the root cells.